2012
DOI: 10.1177/1545109712448217
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Depressive and Other Central Nervous System Symptoms in HIV-Infected Patients Treated with HAART in Spain

Abstract: This study was conducted to assess the prevalence of depressive symptoms, sleep disturbances, and subjective cognitive complaints in patients with HIV receiving highly active antiretroviral therapy. Participants completed the "Center for Epidemiological Studies Depression Scale" (CES-D) and a questionnaire on sleep disturbances and subjective cognitive complaints. Mean age of the 799 participants was 43.7 years and 67% were men. Adjusted prevalence of CES-D was 35.4% (95% confidence interval [CI]: 32.0-38.7), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 58 publications
1
6
1
Order By: Relevance
“…The prevalence of co-occurring anxiety and depression in PLWHA is 80%, higher than the 34% mean depression and anxiety in Pakistan's general population ( 50 ). In addition, the prevalence of 89.9% depression in this study is greater than the prevalence reported by Ethiopian, Spanish, Indian, Cameron, Brazilian, Conakry (capital of Guinea), USA, Denmark, Albania, China studies in which prevalence were reported to be 32, 35.4, 58.1, 28.5, 59, 16.9, 43.9, 38, 58.75, and 73.1% respectively ( 16 , 19 22 , 26 , 51 ). Likewise, the prevalence of anxiety reported in this research is 80.3%, which is higher than reported by Ethiopian, USA, Canada, China, Thailand, Brazil, Western Europe, South African studies in which prevalence were reported to be 32.4, 33, 33.4, 49, 16.3, 12.6, 33.3, and 30.6% respectively ( 26 , 52 , 53 ).…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…The prevalence of co-occurring anxiety and depression in PLWHA is 80%, higher than the 34% mean depression and anxiety in Pakistan's general population ( 50 ). In addition, the prevalence of 89.9% depression in this study is greater than the prevalence reported by Ethiopian, Spanish, Indian, Cameron, Brazilian, Conakry (capital of Guinea), USA, Denmark, Albania, China studies in which prevalence were reported to be 32, 35.4, 58.1, 28.5, 59, 16.9, 43.9, 38, 58.75, and 73.1% respectively ( 16 , 19 22 , 26 , 51 ). Likewise, the prevalence of anxiety reported in this research is 80.3%, which is higher than reported by Ethiopian, USA, Canada, China, Thailand, Brazil, Western Europe, South African studies in which prevalence were reported to be 32.4, 33, 33.4, 49, 16.3, 12.6, 33.3, and 30.6% respectively ( 26 , 52 , 53 ).…”
Section: Discussioncontrasting
confidence: 65%
“…It was associated with higher viral HIV loads, lower CD4 T lymphocyte counts, and affected adherence that predicts disease progression and mortality (16)(17)(18). A recent Ethiopian study reported 32% depression and 34% anxiety in 2019 (16), a Spanish study reported 35.4% depression in 2012 (19), Indian study reported 58.1% depression in 2014 (20). In 2017, Cameron, Brazilian, and Chinese studies reported 28.5, 59, and 80%, respectively, depression in PLWHA (21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…Twenty-six publications reported HBV infection prevalence [63, 65, 69, 71, 79-81, 89, 102, 106, 110, 123, 141, 144, 147, 150, 151, 154, 157, 159, 162, 165, 170, 172, 174, 175]. HBV infection was defined in 72% of individual studies as positive by HBV surface antigen test (see Supplemental Table S7 for all definitions).…”
Section: Resultsmentioning
confidence: 99%
“…Recent surveys on depression among patients with HIV/AIDS in developed countries have also suggested that the prevalence rate in the USA was 13.74% in 2018,12 whereas it was 35.4% in Spain in 201213 and about 22% in Australia in 2003 14. Moreover, in developing countries such as Mexico, the prevalence rate was 27% in 2017,5 and 59.9% and 80.6% in Brazil and China, respectively, also in 2017 15 16.…”
Section: Introductionmentioning
confidence: 99%